Graphitic‐Carbon Layers on Oxides: Toward Stable Heterogeneous Catalysts for Biomass Conversion Reactions1. Issue 27 (14th May 2015) - Xiong, Haifeng; Schwartz, Thomas J.; Andersen, Nalin I.; Dumesic, James A.; Datye, Abhaya K.
Abstract Conversion of biomass‐derived molecules involves catalytic reactions under harsh conditions in the liquid phase (e.g., temperatures of 250 °C and possibly under either acidic or basic conditions). Conventional oxide‐supported catalysts undergo pore structure collapse and surface area reduction leading to deactivation under these conditions. Here we demonstrate an approach to deposit graphitic carbon to protect the oxide surface. The heterogeneous catalysts supported on the graphitic carbon/oxide composite exhibit excellent stability (even under acidic conditions) for biomass conversion reactions.